Social Change: Toward an Informed and Critical Understanding of Social Justice and the Capabilities Approach in Community Psychology. Issue 1 (March 2016) - Munger, Felix; MacLeod, Tim; Loomis, Colleen
Abstract: Community psychology has long been concerned with social justice. However, deployments of this term are often vague and undertheorized. To address this weakness in the field's knowledge body we explored John Rawls's theory of social justice and Amartya Sen's economic theory of the capabilities approach and evaluated each for its applicability to community psychology theory, research, and action. Our unpacking of the philosophical and political underpinnings of Rawlsian theory of social justice resulted in identifying characteristics that limit the theory's utility in community psychology, particularly in its implications for action. Our analysis of the capability approach proposed by Amartya Sen revealed a framework that operationalizes social justice in both research and action, and we elaborate on this point. Going beyond benefits to community psychology in adopting the capabilities approach, we posit a bi‐directional relationship and discuss how community psychology might also contribute to the capabilities approach. We conclude by suggesting that community psychology could benefit from a manifesto or proclamation that provides a historical background of social justice and critiques the focus on the economic, sociological, and philosophical theories that inform present‐day conceptualizations (and lack thereof) of social justice for community psychology.